Monkeypox virus protein OPG188 antagonizes cGAS–STING antiviral signaling pathway to mediate immune evasion - Zhaoyi Pan; Shujuan Zhang; Xianbo Geng; Na Wang; Lijiang Zhang; Luyao Wang; Chunhong Yin; Huijiao Zhang; Shujun Liu; Ling Zhang; Jing Fan; Guangjian Xue; et al. (Proceedings of the National Academy of Sciences, 2026)
Innate immune evasion is critical for productive viral replication. Activation of the cGAS–STING antiviral signaling pathway and its downstream effector genes plays a pivotal role in restricting viral replication during early DNA virus infection. Through a comprehensive genomic screen of monkeypox virus (MPXV), we identified three viral genes, OPG147, OPG188, and OPG200, whose expression potently suppresses cGAS–STING pathway activation. Notably, the N-terminal domain of the Poxin protein encoded by OPG188 exhibits nuclease activity and cleaves the cyclic dinucleotide second messenger 2′3′-cGAMP. Using site-directed mutagenesis, we further delineated nine conserved regions and four key amino acid residues—H15, K140, R182, and I79—within Poxin that are essential for antagonism of cGAS–STING signaling. Moreover, via molecular docking and high-throughput screening of 7,155 small molecules targeting the catalytic pocket of Poxin, we identified two compounds that competitively bind to Poxin, inhibiting its cGAMP—degrading activity and consequently restoring cGAS–STING-mediated antiviral signaling upon MPXV infection. Collectively, these findings underscore the pivotal role of OPG188 in modulating antiviral immune responses and highlight NAD + and Theaflavin-3’-gallate as promising candidates for the development of anti-MPXV therapeutics.